Kevin Coleman and Daniel James (eds.), Capitalism and the Camera: Essays on Photography and Extraction: Verso, 2021 - Petsini, Penelope (Design/Arts/Culture, 2023)
<span class="s2" style="line-height: 14.399999618530273px; font-family: ’Calibri Light’; caret-color: #000000; color: #000000; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">Is it possible that capitalism and photography share more than just a historical timeline, but also an inherent connection in their modes of operation? <span class="s2" style="line-height: 14.399999618530273px; font-family: ’Calibri Light’; caret-color: #000000; color: #000000; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">Does a comprehensive understanding of the origins of photography necessitate an exploration of the imperial violence and rights that underlie its inception? To what extent can photography, a medium often intertwined with capitalism’s alluring influence, be effectively employed to conceptualize and construct alternative image-worlds? Can it serve as a catalyst for inspiring movements aimed at fostering greater freedom and equality across societal boundaries? In transcending its conventional role as a mere recording tool, can the camera assume a transformative role in expanding freedom and equality within society? These are among the critical inquiries posed by this thought-provoking book, compelling readers to engage in a discerning examination of the intricate connections between image production, economic systems, and societal metamorphosis.